Bringing older consumers onboard to online banking: a generational cohort comparison. Issue 3 (4th March 2022) - Jiang, Mengtian; Rifon, Nora J.; Cotten, Shelia R.; Alhabash, Saleem; Tsai, Hsin-Yi Sandy; Shillair, Ruth; LaRose, Robert
ABSTRACT: Though online banking has become more pervasive in U.S. society, little research has examined how different generational cohorts perceive and use online banking. This study examines differences in online banking perceptions and intentions across three generational cohorts in the U.S.: Silent and G.I. generation (SGI) (born 1945 or earlier), older Boomers (1946–1954), and Millennials (1977–1992). Guided by the Technology Acceptance Model and Protection Motivation Theory, it tests a model that identifies factors that influence each generation's acceptance and use of online banking. An online survey of 558 U.S. MTurk workers within three generational cohorts provided data for this study. Findings showed that coping appraisals (i.e., coping self-efficacy and response efficacy) were positive predictors of online banking intentions via reduced barrier perceptions and increased trust perceptions for all ages. Nevertheless, threat appraisals were not negative predictors of online banking intentions via any online banking perceptions. Results also identified generational differences by showing that coping appraisals only increased online banking intentions via enhanced benefit perceptions for Boomers and Millennials, not SGIs. Furthermore, benefit perceptions mattered most to Millennials, followed by Boomers, and did not influence online banking intentions for SGIs. Trust mattered most to SGIs, followed by Boomers, and did not matter to Millennials. This study contributes to our understanding of factors that can help bring older consumers onboard with online banking compared to younger consumers.